EFFECT OF ACOUSTIC RADIATION FORCES ON LIQUID DROPLETS IMMERSED IN A FLUID - Zhuk, O.P.; Zhuk, Ya.A. (Reports of the National Academy of Sciences of Ukraine, 2024)
The interaction of two liquid spherical droplets in another fluid at propagation of a plane acoustic wave along the line connecting the centres of these droplets is investigated. The force of acoustic radiation is determined as follows: first, the linear problem of diffraction of the incident primary wave on bodies in the liquid is solved, then the hydrodynamic forces acting on each of the liquid droplets are calculated, followed by averaging these forces over time. To satisfy the boundary conditions on spherical surfaces, the decomposition of the incident and reflected wave potentials into a series of spherical wave functions is used. By using the obtained analytical formula for calculating the force of acoustic radiation, it is established that the direction and magnitude of the acoustic radiation force can vary depending on the frequency of the incident wave.